Stabilised Control of Converter Interfaced DERs for Reliable Operation of Microgrid and Microgrid Clusters - John, Blessy (Curtin University, 2018)
This thesis aims to achieve a stabilised control of converter interfaced DER for the reliable and resilient operation of microgrid and microgrid clusters. The suitability of voltage and current control for VSCs is evaluated and corrective measures are proposed to stabilise converter operation. Furthermore, the accurate power demand distribution in islanded MGs and interconnected MGs are ensured by advanced control strategies. The proposal presented in the thesis is verified both through simulation and experimental work.